2007
DOI: 10.1177/0165551506070706
|View full text |Cite
|
Sign up to set email alerts
|

The wisdom hierarchy: representations of the DIKW hierarchy

Abstract: This paper revisits the data-information-knowledge-wisdom (DIKW) hierarchy by examining the articulation of the hierarchy in a number of widely read textbooks, and analysing their statements about the nature of data, information, knowledge, and wisdom. The hierarchy referred to variously as the ‘Knowledge Hierarchy’, the ‘Information Hierarchy’ and the ‘Knowledge Pyramid’ is one of the fundamental, widely recognized and ‘taken-for-granted’ models in the information and knowledge literatures. It is often quoted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
722
0
77

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,274 publications
(894 citation statements)
references
References 27 publications
(28 reference statements)
6
722
0
77
Order By: Relevance
“…The assumption is that data can be used to create information; information can be used to create knowledge, and knowledge can be used to create wisdom (Rowley, 2007). (Rowley, 2007) Ackoff (1989) whom this pyramid is attributed to, argues that although there is a tendency to use these concepts interchangeably, not only they are different but they also form a hierarchy of increasing value. The distinction between data/information and knowledge according to Nissen (2006) is specifically obvious where tacit knowledge is involved.…”
Section: What Is Knowledge?mentioning
confidence: 99%
“…The assumption is that data can be used to create information; information can be used to create knowledge, and knowledge can be used to create wisdom (Rowley, 2007). (Rowley, 2007) Ackoff (1989) whom this pyramid is attributed to, argues that although there is a tendency to use these concepts interchangeably, not only they are different but they also form a hierarchy of increasing value. The distinction between data/information and knowledge according to Nissen (2006) is specifically obvious where tacit knowledge is involved.…”
Section: What Is Knowledge?mentioning
confidence: 99%
“…This seems to have been lost from most subsequent presentation of the hierarchy. Rowley points out that most commentators have suggested that understanding is not a separate level [3], while Frické simply notes that it is not typically included [4]. And certainly, understanding is not a distinct state, divorced from the others: as Winograd and Flores put it, "what we understand is based on what we know, and what we already know comes from being able to understand" [5].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge management (KM) is one of the emerging topics of academic and professional discourse in many fields of knowledge, including cognitive sciences, sociology, management science, information science (IS), knowledge engineering, artificial intelligence, and economics [6,18,22,23,33,39,41] Knowledge integration can broadly be defined as the processes by which several individuals combine their information and uniquely held knowledge to create new knowledge; and also Knowledge management (KM) is considered a strategic and value-added endeavor for improving an organization's effectiveness in the changing social and business environment [14]. Drucker [11,12] described knowledge, rather than capital or labor as the only meaningful resource in the knowledge society, and Senge [36] has warned that many organizations are unable to function as knowledge based organizations, because they suffer from learning disabilities.…”
Section: Theoretical Background Of Knowledge Managementmentioning
confidence: 99%